Joshua Lund. The Mestizo State: Reading Race in Modern Mexico. Minneapolis: U of Minnesota P, 2012. xx + 217 pp. - Miguel Ángel González-Abellás (Studies in 20th & 21st Century Literature, 2014)
Joshua Lund. The Mestizo State: Reading Race in Modern Mexico. Minneapolis: U of Minnesota P, 2012. xx + 217 pp.
Keywords: Mexican literature; mestizaje; race; national identity